2018
DOI: 10.3847/1538-4357/aab8fe
|View full text |Cite
|
Sign up to set email alerts
|

K2 Ultracool Dwarfs Survey. III. White Light Flares Are Ubiquitous in M6-L0 Dwarfs

Abstract: We report the white light flare rates for 10 ultracool dwarfs (UCDs) using Kepler K2 short cadence data. Among our sample stars, two have spectral type M6, three are M7, three are M8 and two are L0. Most of our targets are old low mass stars. We identify a total of 283 flares in all of the stars in our sample, with Kepler energies in the range log E Kp ∼(29 -33.5) erg. Using the maximum-likelihood method of line fitting, we find that the flare frequency distribution (FFD) for each star in our sample follows a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(171 citation statements)
references
References 92 publications
12
155
3
1
Order By: Relevance
“…From this we estimate ∆V ∼ −10 and ∆U ∼ −15. This is consequently the second largest observed white-light flare from an L dwarf, following ASASSN-16ae (∆V=-11 Schmidt et al 2016), and larger than those observed with Kepler (Gizis et al 2013(Gizis et al , 2017aPaudel et al 2018).…”
Section: Amplitude and Durationmentioning
confidence: 71%
See 3 more Smart Citations
“…From this we estimate ∆V ∼ −10 and ∆U ∼ −15. This is consequently the second largest observed white-light flare from an L dwarf, following ASASSN-16ae (∆V=-11 Schmidt et al 2016), and larger than those observed with Kepler (Gizis et al 2013(Gizis et al , 2017aPaudel et al 2018).…”
Section: Amplitude and Durationmentioning
confidence: 71%
“…Many ultracool dwarfs which show activity such as radio emission and flaring also tend to be fast rotators, with rotation periods on the order of hours. However, neither the L1 dwarf SDSSp J005406.55-003101.8 (Gizis et al 2017a) nor the L0 dwarf J12321827-0951502 (Paudel et al 2018) showed any sign of rapid rotation when observed by K2, despite showing large amplitude white-light flares. Consequently, we do not attempt to predict whether ULAS J2249-0112 is a fast rotator.…”
Section: Magnetic Activity Of L Dwarfsmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite the difficulty of characterizing flares on the lowest-mass stars, studies have found them to be common (e.g. Schmidt et al 2014Schmidt et al , 2016Gizis et al 2017;Vida et al 2017;Paudel et al 2018Paudel et al , 2019.…”
Section: Resultsmentioning
confidence: 99%